The global cash waqf: a tool against poverty in Muslim countries. (8th February 2021) - Saiti, Buerhan; Dembele, Adama; Bulut, Mehmet
Abstract : Purpose: The problem of poverty in the Muslim world has been posing multi-faceted challenges to the life of individuals and the relations of people. Although this problem has been gaining scholarly attention and raised in relation to various issues ranging from social injustice, rampant corruption, societal instability, wide social polarization and insurgent movements that affect the regional peace and stability at large, neither effective economic mechanism proposed nor implemented to address the problem effectively. In this regard, it is also important to appreciate the recent initiations in the field of Islamic economics to present an optional view to the existing and alien economic models in the Muslim world. Therefore, the purpose of this study is to fill up this research gap by proposing a model of mobilizing funds through the global cash- waqf institution. Design/methodology/approach: The study adopts content analysis to construct this global cash waqf model for poverty alleviation in Muslim countries. Findings: The "global cash- waqf model" was proposed as an alternative that could be implemented and used to overcome the poverty matter in Muslim countries. It is assumed that the model will facilitate the fund mobilization among Muslim countries, which in return is going to assure full distribution and redistribution of wealth to eradicate the poverty in the Muslim world. The model was structured with a global vision in both the collection side and the distribution side. Originality/value: The model will facilitate the fund's mobilization among Muslim countries, which in return achieves an Islamic goal of distribution and redistribution of wealth to assure the well-being of all humanities in the society.